World Development Indicators 2000 - World Bank (The World Bank, 2000)
This is the fourth annual edition of the World Bank's statistical reference. It provides an expanded view of the world economy for 148 countries with chapters focusing on world view, people, environment, economy, states and markets, and global links as well as introductions highlighting recent research on major development issues. This edition includes some key indicators for 1999. This report aims to make statistics lively and comprehensive-to paint a picture of the world and its people. The numbers in this book tell the reader that people in most places are living longer, but that in countries gripped by the HIV/AIDS epidemic, life expectancies are declining. Average incomes continue to rise for most developing countries, but some of the poorest have slipped backwards, subjecting millions more to extreme poverty. It can also be seen that the developing countries are becoming more important participants in the global economy. But the picture is flawed because too often the data are incomplete or unreliable or entirely unavailable. Recognizing the many flaws in the statistical system and the need to address them directly by improving the capacity of countries to produce statistics, a consortium of more than 90 countries and international organizations has come together and pledged to increase the resources for statistical capacity building in developing countries. Hence future editions of this report may prove even more useful